How to Make Money with Youtube - Brad; Schepp Debra (American : MC Graw Hill, 2009)
1. You too can be a youtube star
2. Marketing yourself through youtube
3.Marketing your company on youtube
4. Creating youtube vidieos
5. Promoting and distributing your videos
6. Youtube: Your new revenues stream
7. Other videos - sharing sites and the future of youtube
Contents